Therapeutic Challenges for Elderly Patients with Primary Hyperparathyroidism. (23rd October 2019) - Sluis, Kenneth; Kim, Hyon; He, Yuling; Wong, Beatrice; Wang, Xiangbing
Abstract : Primary hyperparathyroidism (PHPT) predominantly affects older adults, and parathyroidectomy can achieve definitive cure in symptomatic PHPT and asymptomatic meeting surgical criteria. As the population continues to age, the treatment of PHPT in octogenarians and nonagenarians presents a clinical conundrum. This case series presents the management of eight patients 85 years of age and older diagnosed with PHPT. A retrospective chart review of patients diagnosed with primary hyperparathyroidism were identified in a single institution. Those patients 85 years of age and older who were followed up for over one year were included in this case series. The literature on treatment options for this age group was also reviewed. Eight cases of PHPT patients aged 88 ± 2.5 years old with a follow-up average of 5.6 ± 4.4 years were reported in our case series. Six PHPT patients were medically managed and two PHPT patients underwent parathyroid resection. Most of the medically managed PHPT patients except for one had long-term stability of disease for over five years. The treatment of PHPT diagnosed in patients over 85 years of age presents a clinical challenge for which there is no clear consensus guideline. Our case series supports that medical therapy is a feasible option for PHPT patients over 85 years old.